2022
DOI: 10.3390/w14030416
|View full text |Cite
|
Sign up to set email alerts
|

Potential Sea Level Rise Inundation in the Mediterranean: From Susceptibility Assessment to Risk Scenarios for Policy Action

Abstract: Coastal ecosystems and anthropic activities are prone to be affected by the negative impact of marine-related processes induced by climate change, such as erosion, flooding and permanent inundation. Studies aiming at defining potential risk scenarios represent a valuable tool for the identification of the most suitable coastal adaptation measures. After outlining sea level rise implications at the Mediterranean scale, this paper deals with inundation risk scenarios for the years 2050 and 2100 for the north-eas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 67 publications
1
10
0
Order By: Relevance
“…It is the belief of stakeholders that the disconnect from scientific data on SLR also extends to decision-makers, causing significant gaps in awareness and even major misconceptions. This output is in line with the work of Rizzo et al ( 2022 ) who found that in the Mediterranean there is a need for creating a bridge to allow policy-makers to understand and adopt the results of scientific data and risk assessments regarding SLR. Data are therefore important and useful for a wide range of local stakeholders and high-quality information is important for building credibility and for encouraging communities to act against SLR.…”
Section: Discussionsupporting
confidence: 86%
“…It is the belief of stakeholders that the disconnect from scientific data on SLR also extends to decision-makers, causing significant gaps in awareness and even major misconceptions. This output is in line with the work of Rizzo et al ( 2022 ) who found that in the Mediterranean there is a need for creating a bridge to allow policy-makers to understand and adopt the results of scientific data and risk assessments regarding SLR. Data are therefore important and useful for a wide range of local stakeholders and high-quality information is important for building credibility and for encouraging communities to act against SLR.…”
Section: Discussionsupporting
confidence: 86%
“…It requires human intervention to reduce GHG emissions under climate-policy socioeconomic reference scenarios [45]. However, the RCP8.5 is defined as a high pathway that leads to radiative forcing higher than 8.5 W•m −2 in 2100 [11] without a climate change policy [46].…”
Section: Cnrm-cm5 Noresm1-m Cm5a-mr Ec-earth Mpi-esm-lrmentioning
confidence: 99%
“…Numerous papers affirmed that climate change would affect the Mediterranean countries [9][10][11][12], including Tunisia, more than other regions [13,14]. The Mediterranean region is considered a climate change hotspot [14] where its warming will occur 20% faster than the global average [13].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, sea‐level rise due to global warming is expected to have a series of negative effects on the settlements close to the shoreline, as well as the deltas all over the world (Hereher, 2015). In particular, the Mediterranean coastal areas are highly exposed to negative coastal processes such as erosion, which, in turn, are strongly affected by increases in mean sea level due to climate change events (Rizzo et al, 2022). Under current conditions, many WHSs are at risk of coastline erosion associated with storm surges, wave action, currents and high tides (Franco, 1996; Porotov, 2007; Reimann et al, 2018).…”
Section: Introductionmentioning
confidence: 99%